2013
DOI: 10.1017/s1461145713001053
|View full text |Cite
|
Sign up to set email alerts
|

Course of weight gain and metabolic abnormalities in first treated episode of psychosis: the first year is a critical period for development of cardiovascular risk factors

Abstract: Data on the long-term metabolic side-effects associated with antipsychotics are scarce. Prospective longitudinal studies in medication-naive patients with a first episode of psychosis are a valuable source of information as they provide an assessment prior to the antipsychotic exposure and minimize the effect of potential confounding factors. The aim of this study was to assess the course of weight gain and the incidence of metabolic abnormalities during the first 3 yr of antipsychotic treatment. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 40 publications
(38 reference statements)
10
79
0
5
Order By: Relevance
“…1,13 Such medications have been associated with clinically significant weight gain in as few as 10 to 12 weeks. 1,8,[14][15][16][17][18][19][20][21] Among forensic patients, Haw and Rowell 10 reported that obesity was related to the prescription of 1 or more AP, particularly valproate. Ojala et al 22 found that, among Finnish forensic patients (89% male, 92% diagnosed with schizophrenia), metabolic syndrome and obesity were more common among those taking regular doses of atypical APs, controlling for age, sex, and clinical diagnosis, which were not themselves related to BMI.…”
Section: Limitationsmentioning
confidence: 99%
“…1,13 Such medications have been associated with clinically significant weight gain in as few as 10 to 12 weeks. 1,8,[14][15][16][17][18][19][20][21] Among forensic patients, Haw and Rowell 10 reported that obesity was related to the prescription of 1 or more AP, particularly valproate. Ojala et al 22 found that, among Finnish forensic patients (89% male, 92% diagnosed with schizophrenia), metabolic syndrome and obesity were more common among those taking regular doses of atypical APs, controlling for age, sex, and clinical diagnosis, which were not themselves related to BMI.…”
Section: Limitationsmentioning
confidence: 99%
“…Weight gaining is a SE due to neuroleptics and can be explained by the improvement of the appetite. 4.65% of the patients experienced an increase of appetite; a number which is smaller than the 78% of Pérez-Iglesias et al' in Spain [29]. This variation is explainable by difference of classes of the neuroleptics prescribed in both settings.…”
Section: Discussionmentioning
confidence: 72%
“…This Spanish study compared weight gain resulting from treatment with risperidone, haloperidol and olanzapine. In the first three months, olanzapine resulted in faster weight gain than risperidone or haloperidol, but after over 12 months, the amount of weight gain resulting from treatment with these drugs (8-10 kg) was not significantly different (Perez-Iglesias et al, 2008;Pérez-Iglesias et al, 2014). These data suggest that there is a shared general mechanism of weight gain induced by antipsychotics.…”
Section: Role Of Medication In Weight Gainmentioning
confidence: 77%
“…Indeed, weight gain can be excessive (about 12 kg body weight over a course of three years; cf. Pérez-Iglesias et al, 2014) and is typically observed after psychotropic treatment begins, suggesting an interaction between psychiatric disease and medication.…”
Section: The Clinical Consequences Of Weight Gainmentioning
confidence: 99%
See 1 more Smart Citation